ANALYZING MENTAL HEALTH DISORDER RATES AMONG PRIVATE SECTOR MEDICAL STUDENTS: TACKLING GENDER DISPARITIES. : JPUMHS; 2025:15:01,4-12. http://doi.org/10.46536/jpumhs/2025/15.01.589 - Mahnoor Tariq1, Kainat Javed2, Jannat Tariq 3, Ayesha Shahid Butt 4, Zarmin Ali5, Muhammad Ashir Naveed6 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
ABSTRACT BACKGROUND: This study investigates the frequency of Mental Health Disorders among students at Private sector medical college and university with a specific focus on the mental health challenges faced by undergraduate students. OBJECTIVE: This study aims to explore the prevalence of these mental health disorders between university students and to identify key risk factors, providing insights for targeted interventions to support student well-being. METHODOLOGY: A total of 247 students (166 females and 81 male) from different programs, including MBBS (132 participants), BDS (44 participants), and other medical disciplines (71 participants), participated in this cross-sectional study. Random sampling was used to choose participants according to their educational attainment, gender, and field of study. Students who had used on-campus wellness and counseling services met the inclusion criterion, whereas those who had never used these services were not included. This study employed six established instruments to evaluate mental health conditions, including the GAD-7 (generalized anxiety disorder-7) to screen for generalized anxiety disorder, the PHQ 9 (patient health questionnaire-9) to gauge the severity of depression, and the PHQ-15 to measure somatic symptoms. Obsessive-compulsive disorder symptoms were evaluated using the OCI-R (obsessive-compulsive inventory-n revised). SPIN was used for social anxiety, and the severity measures for specific phobia and panic disorder, both showing strong validity and reliability. The DAST-10 (drug abuse screening test) was used to assess substance use. RESULTS: Results indicated a high prevalence of mental health disorders: 58.9% for somatic symptom disorder, 39.9% for depression, 22.3% for generalized anxiety disorder, and 48% for obsessive-compulsive disorder and 4.1% in substance-use disorder. Notably, female students exhibited significantly higher scores in depression and anxiety disorders compared to their male counterparts. Significant comorbidities were observed, with depression frequently co-occurring with somatic symptom disorder and anxiety disorders. CONCLUSION: Enhancing mental health resources and support systems within university settings is crucial to promote student well-being and academic success. Further research is recommended to explore the underlying causes of these gender disparities in mental health.